2022
DOI: 10.1186/s12911-022-01840-7
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators for disease registry systems: a mixed-method study

Abstract: Background A Disease Registry System (DRS) is a system that collects standard data on a specific disease with an organized method for specific purposes in a population. Barriers and facilitators for DRSs are different according to the health system of each country, and identifying these factors is necessary to improve DRSs, so the purpose of this study was to identify and prioritize these factors. Methods First, by conducting 13 interviews with DRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Data barriers remain common challenges in public health research, despite efforts to facilitate improvements [57, 58]. As Puducherry has the advantage of a relatively small size and well-connected healthcare facilities, efforts need to be taken to improve a central, disease specific data collection system, incorporating all the healthcare facilities in the State [59].…”
Section: Discussionmentioning
confidence: 99%
“…Data barriers remain common challenges in public health research, despite efforts to facilitate improvements [57, 58]. As Puducherry has the advantage of a relatively small size and well-connected healthcare facilities, efforts need to be taken to improve a central, disease specific data collection system, incorporating all the healthcare facilities in the State [59].…”
Section: Discussionmentioning
confidence: 99%
“…First, we have demonstrated a large variability in data collection processes, inclusion criteria, and definitions of parameters. Data harmonisation (i.e., merging data with varying formats and definitions) and recoding would be necessary, although it would result in less specific data and probably the loss of information ( 3 , 19 ). The balance between comprehensiveness and feasibility remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating data quality, giving feedback and correcting data is time consuming. Other studies have reported similar problems related to data quality evaluation [57,58]. In this case, hiring a qualified person for these functions will be required.…”
Section: Limitationsmentioning
confidence: 90%
“…Furthermore, the organization of variables in different questionnaires was not approved by experts in some cases. According to previous studies [57,58], other registries also faced such limitations and this could cause problems in a registry. Therefore, during the pilot, by holding various meetings, the minimum mandatory data and their organization were finalized with the participation of nephrologists.…”
Section: Limitationsmentioning
confidence: 99%